Metabolic and Electrolyte profile in Birth Asphyxia - Dr. Abhishek Kumar Singh; Dr. Bhoopendra Sharma; Dr. Anita Mehta; Dr. Karm Chand Gandhi; Dr. Harish Chandra Tiwari (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: The definition of birth asphyxia is given by the ACOG, AAP includes the existence of 3 factors: Metabolic or mixed acidemia (pH<7) which is determined by umbilical cord arterial blood samples. The major causes of neonatal seizures are Hypoxic-ischemic encephalopathy (HIE), which represents about 50% of the causes of neonatal seizures. Metabolic abnormalities, infection, intracranial hemorrhage, developmental anomalies, and other like inborn errors of metabolism are other causes of neonatal seizures.Material and Methods: A cross-sectional study. This is a hospital-based prospective study conducted at Nehru Hospital, BRD Medical College, Gorakhpur (UP) in the Neonatal Intensive Care Unit of the pediatric department. This study was conducted from July 2018 to July 2019.Result: Prevalence of Hypocalcemia was 7.6%, Prevalence of hypernatremia was 1.3%, Out of 315 patients 32 (10.2%) patients expired and 283 (89.8%) was successfully discharged.Conclusion: No association between Hypocalcemia and Hypomagnesemia Prevalence of hyponatremia was 6.3% and no association between hyponatremia and Hypomagnesemia. The prevalence of hypernatremia was 1.3% and there was no association between hypernatremia and Hypomagnesemia.